Numerical study of flow and heat transfer in curvilinear ducts - Öztop, Hakan Fehmi (Elsevier Science Inc, 2005)
A numerical study was performed to investigate heat transfer and fluid flow in curvilinear shaped duct geometries. SIMPLEM algorithm was used with a non-staggered grid arrangement to solve Navier-Stokes and energy equations in curvilinear coordinates. To obtain grid generation for curvilinear surfaces elliptic grid generation method was used. Two examples were demonstrated for laminar flow regime in the study: First, asymmetric sinusoidal wavy walled duct and second partially inclined duct geometry were chosen. The results show that SIMPLEM algorithm with non-staggered grid arrangement is a useful technique to solve temperature and flow field in curvilinear ducts by using elliptic grid generation method. (c) 2004 Elsevier Inc. All rights reserved.
Keywords: Arbitrary 2-Dimensional Bodies; Algorithm; System